Beta amyloid is focally deposited within the outer basement membrane in the amyloid angiopathy of Alzheimer's disease. An immunoelectron microscopic study. - Yamaguchi, H. (1992)
The fine structure of cerebral amyloid angiopathy, especially in small and presumably early deposits, was examined by immunolabeling of the beta/A4 protein in semithin and ultrathin sections from brains with Alzheimer's disease. The following findings emerged: 1) in large leptomeningeal arteries, small, focal amyloid deposits appear to consist of clusters of delicate (approximately 8 nm diameter) amyloid fibrils, not previously described, in the outermost part of the basement membrane (BM) at the media-adventitia junction; 2) in small leptomeningeal arteries and perforating cortical arterioles, small foci of delicate amyloid fibrils were observed within the BM. They appeared mostly in the outer portion of the BM, around intact smooth muscle cells, rather than in the subendothelial region. In larger and presumably more advanced deposits, coarse amyloid fibrils (approximately 10 nm) occupied the abluminal BM, and adjacent smooth muscle cells showed degeneration; and 3) in capillaries, small amounts of delicate (approximately 8 nm) amyloid fibrils, not previously described, were seen within the BM in the smallest discernible deposits. The BM at these sites was abnormally folded and layered. In larger deposits, amyloid fibrils appeared to extravasate from the outer BM of the capillary into the neuropil and were surrounded by astrocytic foot processes and/or microglia. Our results suggest that vascular amyloid fibrils may first be formed within the abluminal vascular BM, that is, outside of cells. The BM may trap degradative intermediates of the amyloid precursor protein that contain the beta/A4 region, and local proteases may then cleave them further to yield amyloidogenic fragments.